DETERMINANTS OF LOW BIRTH WEIGHT: COMPARISON BETWEEN PERCEPTION AND RECORDS USING THE INDONESIAN DEMOGRAPHIC HEALTH SURVEY DATA - Prayogi, Ahmad Ridoi Yuda; Sebayang, Susy Katikana; Li, Mu (Jurnal Biometrika dan Kependudukan, 2025)
Measuring birth weight in low resource settings is problematic. Mothers' perception of newborn's size is often used as a proxy. This study examines the correlation between weight measured at birth and the mother's perception of her child's size and compare the determinants of low birth weight (LBW) and small birth size using both measures. This study analyzed the 2017 Indonesian Demographic and Health Survey data and examined the list of determinants associated with birth weight. There was a strong correlation between newborn's weight measured at birth and mother's perception of birth size and a high agreement between LBW and perceived small birth size. Both measures, birth order was a significant child factor, and the number of antenatal care (ANC) visits was an important ANC factor. Maternal education was a significant socioeconomic determinant of LBW, while household wealth and improved household latrine were significant determinants of perceived birth size. Mother's perception of birth size can be used as a proxy measurement for a child's birth weight for programmatic purposes in low resource settings where birth weight was difficult to measure.